2015
DOI: 10.1016/j.ejvs.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Branch Vessels in Aortic Type B Dissection: An in vitro Study

Abstract: Increasing antegrade outflow through a branch vessel originating from the false lumen when no distal re-entry tear is present results in an expansion of the cross sectional false lumen area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…These concepts have been proposed 60 years ago by Shaw 43 and De Bakey 44 and are currently finding a revival. 41,45 …”
Section: Discussionmentioning
confidence: 99%
“…These concepts have been proposed 60 years ago by Shaw 43 and De Bakey 44 and are currently finding a revival. 41,45 …”
Section: Discussionmentioning
confidence: 99%
“…Since many AD patients have visceral side branches (including important ones such as the celiac trunk) originating from the FL, and this was reported to be significant related to aortic enlargement [ 5 , 29 ], we assessed their influence on flow. Our results showed that the incidence of FL side branches increased the amount of FL flow volume and affected FL flow direction, so that FL flows became more unidirectional (mostly antegrade or retrograde depending on the level of the dissection), primarily affecting the percentage of retrograde diastolic FL flow.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro circulatory system was previously validated with respect to simulating the human circulatory system. [19][20][21][22] Fig 1 shows a systematic representation of the in vitro circulatory system, which consists of a pneumatically driven pulsatile pump, a ball valve, a compliance air chamber, an arterial stenosis model (a removable tube for inserting the stenosis), a pressure band to simulate peripheral resistance, and a collateral system with intrinsic peripheral resistance. The following degrees of stenosis were used at two different lengths (2 and 8 cm): 50%, 70%, 80%, and 90%; these stenosis models were easily switched in the arterial stenosis model.…”
Section: Methodsmentioning
confidence: 99%